The Effect of Earmuff and Earplug Use on Preterm Infants Towards Oxygen Saturation and Pulse - Bayhakki Bayhakki; Dini Maulinda; Deswinda Deswinda (Jurnal Keperawatan Padjadjaran, 2022)
Background: A bright circumstance, cold temperatures with loud noise andmany activities around can inﬂuence oxygen saturation and pulse in pretermbaby.Purpose: This study aimed to identify the eﬀect of using earmuﬀs andearplugs on the physiological response of preterm infants.Methods: This crossover study involved 15 medically stable preterm infantstreated in a closed incubator. It used the consecutive sampling techniquewhere the babies’ physiological response using Neonatal Pulse Oximetri wasobserved for 30 seconds every 15 minutes for two hours of using earmuﬀsand earplugs.Results: The result of repeated ANOVA analysis showed that there is nosignifcant diﬀerence of pulse repetition frequency before, during, and afterusing the earmuﬀ and earplug to preterm infants. Meanwhile, statistically,there was a diﬀerence in the mean of oxygen saturation during and afterusing the earmuﬀ with p = 0.019.Conclusion: The use of ear protection (earmuﬀ and earplug) could assistand support premature infants in maintaining physiological condition.Earplugs are considered better than earmuﬀs for maintaining a preterminfant’s physiological condition.